Elevated liver transaminase levels prolong hospital stay in dengue patients: retrospective cohort study - Alnweiri, Abdelrahman MS; Prihartono, Nurhayati A. (Universitas Gadjah Mada, 2025)
Purpose: To evaluate the public health impact of elevated liver transaminases (AST/ALT >35 U/L) on hospitalization duration in adult dengue patients in Indonesia’s resource-constrained settings. Methods: Retrospective cohort study of 786 confirmed dengue patients at Ummi Hospital, Bogor (2021–2023). We analyzed demographics, comorbidities, hepatoprotective therapy, and AST/ALT levels. Prolonged stay was defined as ≥5 days. Multivariate logistic regression identified predictors of prolonged length of stay (LOS). Results: 41.9% had elevated transaminases. Patients with enzyme elevations had longer hospital stays than those with normal levels. Non-comorbid patients with elevated enzymes were significantly more likely to experience prolonged hospitalization. Comorbidities markedly increased the risk of extended stays, while hepatoprotective therapy reduced it. Nationally, this could save 105,000 bed-days annually. Conclusion: Elevated transaminases independently predict prolonged dengue hospitalization. Routine liver monitoring and hepatoprotective therapy may optimize bed utilization in Indonesian hospitals.